ON THE OPTIMUM BUOYANCY WEIGHT RELATION FOR A BOTTOM TRAWL. - NARAYANAPPA, G; SATYANARAYANA, A V.V (Fishery Technology, 2016)
Comparative fishing operations were carried out with 0.55; 0.75 and 1.00 buoyancy-weight relations of bottom trawl in order to find out the optimum relation. Two nets Viz, 18.26 m. (60’) two seam nylon and 16.16 m. (23’) two seam cotton trawls were used for the experiment. The results showed that the total catch per trawling hour with 0.75 B-W relation was 16.5% and 32.08% more than that with 0.55 and 1.00 B-W relation for nylon net used. A similar trend was noticed with cotton trawl also as the catch rate with 0.75 B-W relation was 13.89% and 25.78% more than that with 0.55 and 1.00 B-W relation. However, the analysis of catch composition indicated that the off bottom fishes like lactarius, upenoides sp., synagris sp. etc., were of more percentage with 1.00 B-W relation, near bottom fish like saurida, sciaenids etc., were more with 0.75 B-W relation, while the bottom fishes like soles, prawns, skate3 and rays etc., were more with 0.55 B-W relation.